Effects of phospholipid complexes of total flavonoids from Persimmon (Diospyros kaki L.) leaves on experimental atherosclerosis rats. (15th September 2016) - Zhang, Kexia; Zhang, Yuanyuan; Zhang, Meiyu; Gu, Liqiang; Liu, Ziying; Jia, Jingming; Chen, Xiaohui
Abstract: The total flavonoids from Persimmon leaves (PLF), extracted from the leaves of Diospyros kaki L. Dispryosl and Ebenaceae, is reported to possess many beneficial health effects. However, the oral bioavailability of PLF is relatively low due to its poor solubility. In the present study, the phospholipid complexes of total flavonoids from Persimmon leaves (PLF-PC) was prepared to enhance the oral bioavailability of PLF and to evaluate its antiatherosclerotic properties in atherosclerosis rats in comparison to PLF. A HPLC-MS method was developed and validated for the determination of quercetin and kaempferol in rats plasma to assess the oral bioavailability of PLF-PC. The effect of PLF (50 mg/kg/d) and PLF-PC (equivalent to PLF 50 mg/kg/d) on atherosclerosis rats induced by excessive administration of vitamin D (600, 000 IU/kg) and cholesterol (0.5 g/kg/d) was assessed after orally administered for 4 weeks. The relative bioavailabilities of quercetin and kaempferol in PLF-PC relative to PLF were 242% and 337%, respectively. The levels of total cholesterol (TC), triglyceride (TG), low-density lipoprotein-cholesterol (LDL-C), high-density lipoprotein-cholesterol (HDL-C), apolipoprotein A1 (ApoA1) and apolipoprotein B (ApoB) in serum were measured by an automatic biochemistry analyzer. The morphological changes of aorta were observed with optical microscopy. According to the levels of biochemical parameters in serum and the morphological changes of aorta, PLF-PC showed better therapeutic efficacy compared to PLF. Thus, PLF-PC holds a promising potential for increasing the oral bioavailability of PLF. Moreover, PLF-PC exerts better therapeutic potential in the treatment of atherosclerotic disease than PLF. Graphical abstract: